Identification of Wood Degrading Ability and Identity of Fungi Collected from the Danish Technology Institute - University Malaysia Sarawak (DTI-UNIMAS) Field Test Site - Farawahida, Yusup (Universiti Malaysia Sarawak (UNIMAS), 2007)
Wood decay fungi cause billion of ringgit loses each year by destroying wood in forest trees that could be used for timber and also by causing decay in buildings and other wood services. The purpose of this study was to identify fungi which had been collected from DTI- UNIMAS Field Test Site which are Schizophyllllm commllne, Marasmills candidlls, Pestlotiopsis sp and Trametes sp. and these fungi were isolated to evaluate wood decay ability of rubberwood and pelai wood based on weight loss. The ability of rubberwood and pelai wood against Schizophyllllm commllne, Marasmius candidlls, Pestalotiopsis spand Trametes sp was tested on agar-block test (l % MEA agar). These fungi were categorized into different classes based on the percentage of weight loss. The results shows that fungi Marasmills candidus have no ability in degrade pelai wood and 10% no degrade ability towards rubberwood. Schizophyllum commune also shows no ability in degrade pelai wood but 30% no degrade ability towards rubberwood. Meanwhile Pestlotiopsis sp shows 90% no degrading ability against pelai wood and 90% was poor in degrading ability towards rubberwood. Trametes sp had no results due to data had not been determined because of contamination of bacteria and other fungi to all samples.